2012
DOI: 10.1016/j.bbamcr.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate-mediated α1B-adrenoceptor desensitization and phosphorylation. Direct and paracrine/autocrine actions

Abstract: Sphingosine-1-phosphate-induced α1B-adrenergic receptor desensitization and phosphorylation was studied in rat-1 fibroblasts stably expressing enhanced green fluorescent protein-tagged adrenoceptors. Sphingosine-1-phosphate induced adrenoceptor desensitization and phosphorylation through a signaling cascade that involved phosphoinositide 3-kinase and protein kinase C activities. The autocrine/paracrine role of sphingosine-1-phosphate was also studied. It was observed that activation of receptor tyrosine kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
(74 reference statements)
4
9
0
Order By: Relevance
“…PMA and S1P induced a 1B -AR internalization that was markedly diminished by the same treatments, i.e., PKC inhibition, PKC downregulation, and the expression of a GDP-locked dominant-negative Rab9 mutant. These data are consistent with the current idea that PKC is a major mediator of a 1B -AR heterologous desensitization, including receptor phosphorylation and internalization; this can be induced by S1P (Castillo-Badillo et al, 2012 and by a large variety of hormones and neurotransmitters acting through different families of receptors [see Castillo-Badillo et al (2012; García-Sáinz et al (2000; and references therein]. A working model is presented in Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…PMA and S1P induced a 1B -AR internalization that was markedly diminished by the same treatments, i.e., PKC inhibition, PKC downregulation, and the expression of a GDP-locked dominant-negative Rab9 mutant. These data are consistent with the current idea that PKC is a major mediator of a 1B -AR heterologous desensitization, including receptor phosphorylation and internalization; this can be induced by S1P (Castillo-Badillo et al, 2012 and by a large variety of hormones and neurotransmitters acting through different families of receptors [see Castillo-Badillo et al (2012; García-Sáinz et al (2000; and references therein]. A working model is presented in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Fura-2/AM [bis(acetoxymethyl) 2,29-((2-(5-((acetoxymethoxy)carbonyl)oxazol-2-yl)-5-(2-(2-(bis(2-(acetoxymethoxy)-2-oxoethyl)amino)-5-methylphenoxy)ethoxy)benzofuran-6-yl)azanediyl)diacetate]; PubChem 3364574), Dulbecco's modified Eagle's medium, fetal bovine serum albumin, trypsin, antibiotics, and other reagents employed for cell culture were from Life Technologies/ ThermoFisher Scientific. Other reagents were from previously described sources (Castillo-Badillo et al, 2012.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…α 1B -Adrenergic receptor desensitization, phosphorylation, and internalization has been extensively studied and major differences have been observed in these processes when they are triggered either by adrenergic agonists (homologous) or by unrelated agents (heterologous) acting through other GPCRs, receptor tyrosine kinases, nuclear receptors or by direct activation of protein kinase C [ 40 57 ]. Among the GPCRs whose activation induce α 1B -adrenergic receptor phosphorylation and internalization is the sphingosine 1-phosphate S1P1 receptor [ 42 ]. Sphingosine 1-phosphate is a bioactive lipid that functions as a paracrine / autocrine mediator [ 58 ], and through the S1P1 receptor plays cardinal roles in the intense crosstalk that takes place between receptor tyrosine kinases and GPCRs [ 42 , 43 , 58 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, it has been reported that cAMP is involved in desensitization of the b 1 -adrenergic receptor as well as the b 2 -adrenergic receptor, probably via direct phosphorylation of the receptors by the cAMP-dependent protein kinase. 48,49 Castillo-Badillo et al 50 showed that activation of S1P 1 receptors may induce a 1B -AR phosphorylation and desensitization via a mechanism that may involve phosphoinositide 3-kinase (PI3K) and PKC signalling. In the cardiovascular system, these observations suggest that activation of S1P signalling may represent an additional potential protective mechanism as it is known that a 1B -ARs may regulate several processes, such as cardiac muscle and arteriolar smooth muscle contraction, and be implicated in other pathological processes, such as cardiac hypertrophy or ischaemia-induced cardiac arrhythmias and the genesis/ maintenance of hypertension.…”
Section: Cardiovascular Effects Of Acute Hyperglycaemiamentioning
confidence: 99%